Interactions of arboreal yeast endophytes: an unexplored discipline. (August 2016) - Moller, Leandra; Lerm, Barbra; Botha, Alfred
Abstract: The value of healthy forest ecosystems is well known and trees in these systems form symbioses with a variety of living organisms. This review focuses on literature pertaining to the potential interactions of arboreal yeast endophytes with trees and their associated insects. Although very little is known about the symbioses of arboreal yeast endophytes, indications are that some of these unicellular fungi produce plant-growth promoting phytohormones, while others are antagonistic towards phytopathogens or are capable of producing pheromones that affect the behavior of insect herbivores. However, more research needs to be conducted to fully understand the role of arboreal yeast endophytes in ecosystem processes.